KESULITAN DAN SOLUSI DALAM MENULIS SKRIPSI BAHASA INGGRIS (Sebuah Investigasi Berdasarkan Perspektif Mahasiswa dan Dosen di Program Studi Pendidikan Bahasa Inggris, Universitas Pekalongan) - Sarlita Dewi Mtra; Dwi Ario Fajar (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
This research aims to analyze the English Education students’ of Universitas Pekalongan problems  in  writing  final  project  in  English.  The  causes  are  viewed  from  students’  and  the lecturers  perspective  as  the  advisor  and  also  what  are  supposed  to  do  to  help  the  student minimize the problems in writing final project. This study used descriptive qualitative method that fully describe the problems as well as solutions in writing final projects. The deep analysis has been done  from the student’s and the lecturer’s perspectives. After conducting a survey by doing some interviews and distributing questionnaires, we found that there are so many factors that affects the studnts’ difficulties in finishing their final projects.